Distribution of Heavy Metals in the Soils Associated with the Commonly Used Pesticides in Cotton Fields - Saadia Rashid Tariq; Musharaf Shafiq; Ghayoor Abbas Chotana (Scientifica)
Agricultural soils contain both heavy metals and pesticides originating from various agricultural practices. It is quite important to study the relationships between these two classes of compounds. To accomplish this, 52 soil samples were collected from cotton fields and analyzed for their metal contents (Ni, Cu, Co, Pb, Cr, and Cd) and levels of most commonly used pesticides (imidacloprid, acetamiprid, and emamectin). FAAS was used for metal estimation and the pesticides were determined by HPLC equipped with UV detector. The results of the study revealed slightly enhanced levels of Ni and Cd in these samples while the rest of the metals were present within tolerable range. Acetamiprid residues in soil were strongly positively correlated with Cu and negatively correlated with Cr. Similarly, imidacloprid in soil was negatively correlated with Ni. Thus it was evidenced that Cu stabilizes acetamiprid while Cr and Ni facilitate the degradation of acetamiprid and imidacloprid in the soil.